A New Method for Calculating the Voltage Dip Type in Three-Phase Systems - Zhi-Yuan, MA; Zhou, Kai; Wang, Hai-Jing (2018 China International Conference on Electricity Distribution (CICED), 2018)
Voltage dip is one of the severe power quality disturbances, leading to complains from the industry customers. There are kinds of ways to mitigate the effect by voltage dip. Calculating and determining the dip type is the premise of choosing the mitigation method. This paper proposes a new algorithm for calculating the voltage dip type. The algorithm is based on the shapes of Type C and Type D. Apply the new algorithm on comprehensive voltage dips and compare with the typical dip type method to verify the feasibility and correctness.